Efficacy and safety of pegylated liposomal doxorubicin and epirubicin as neoadjuvant chemotherapy for breast cancer - Shen, Yuanyuan; Hua, Qingling; Dong, Menghao; Jin, Wei; Hu, Xueyang; Gu, Kangsheng (Frontiers in Cell and Developmental Biology, 2024)
AimThis study aims to compare the efficiencies and toxicities of pegylated liposomal doxorubicin (PLD) based and epirubicin based chemotherapeutic regimens as neoadjuvant chemotherapy (NAC) for early breast cancer.Patients and methodsWe retrospectively analyzed 391 patients with stage II-III breast cancer who received NAC in multiple centers. The efficiencies and toxicities of PLD and epirubicin based NAC regimens were compared by using both propensity-score matched (PSM) and unmatched data. The status of relevant gene loci was detected through next-generation sequencing (NGS) technology and the correlation between mutations of genes and serious adverse events (AEs) was preliminarily analyzed.ResultsA total of 391 patients were included in this study. Among them, 235 patients received PLD based NAC (PLD group), and the other 156 patients were administrated with EPI based NAC (EPI group). The pathological complete response (pCR) rate of patients in PLD group was significantly higher than EPI group (before PSM:32.3% vs. 23.1%; after PSM:42.5% vs. 24.7%). Most severe AEs of patients in EPI group were more than PLD group (before PSM: 1.3%–37.8% vs. 0%–10.6%; after PSM: 1.4%–37.0% vs. 0%–9.6%). Mutation rates of 7 gene (MTHFR, DPYD, NQO1, ERCC1, UGT1A1, TYMS and TP53) of patients with severe AEs were significantly higher compared with patients with slight AEs (grade 1/2) or without AEs.ConclusionPLD based chemotherapeutic regimen is a viable option for NAC of breast cancer. Epirubicin should be avoided for patients with mutations of some specific genes considering the potential severe AEs.